Road hierarchy with integration of attributes using fuzzy-AHP - Gulgen, Fatih (TAYLOR & FRANCIS LTD, 2014)
Road objects in a network data model are categorised into a hierarchical structure in accordance with their functions and capacities. In this study; five road attributes derived from semantic, geometric and topological properties of network data set (i.e. road class, road length and centralities of degree, closeness and betweenness) are utilised for the creation of road network hierarchy. The relationships with each attributes except road class and their effects on the determination of road importance are analysed by using a distribution graph and the equation of Pearson correlation coefficient. For creating road network hierarchy, integration process is achieved through the application of fuzzy analytic hierarchy process assuming attributes as the fuzzy criteria. The integration process is followed by the calculation of new priority attribute that indicates the importance of road objects. At the end of the process, road class, which is the most important attribute, is also used for the validation of proposed methodology. The results show that the new priority value of a road is superior to its each attribute value in hierarchical organisation.
Keywords: GIS; road network; network analysis; MCDM; AHP; correlation; STREET; SITE; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology